2018
DOI: 10.1007/s11625-018-0532-y
|View full text |Cite
|
Sign up to set email alerts
|

How transdisciplinary projects influence participants’ ways of thinking: a case study on future landscape development

Abstract: Transdisciplinary (TD) approaches have increasingly been promoted in the field of land-use research. However, the theoretical discourse about transdisciplinarity is far more advanced than its implementation in practice. In particular, empirical studies about the effects of concrete TD projects on the participants are rare. We evaluated joint knowledge generation among researchers and non-academics in a TD research programme on urban and landscape development. For the assessment we used standardised questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 35 publications
1
9
0
1
Order By: Relevance
“…2. As also reported by Durham et al (2014) and Tobias et al (2018) we found it quite challenging to initialize the TDR project in terms of getting the right stakeholders on board. Initially stakeholders were difficult to reach by email of phone, emails asking for an interview were rarely considered and our local assistants were only successful in fixing a few interviews appointments in advance by phone.…”
Section: Encountered Difficulties and Strengthssupporting
confidence: 54%
See 1 more Smart Citation
“…2. As also reported by Durham et al (2014) and Tobias et al (2018) we found it quite challenging to initialize the TDR project in terms of getting the right stakeholders on board. Initially stakeholders were difficult to reach by email of phone, emails asking for an interview were rarely considered and our local assistants were only successful in fixing a few interviews appointments in advance by phone.…”
Section: Encountered Difficulties and Strengthssupporting
confidence: 54%
“…In practice, it is challenging to initialize, frame and design the TDR process, selecting appropriate methods for collaboration and knowledge integration among scientists from different disciplines and practitioners (Luthe 2017). Each TDR process needs to be adapted to the given context, the needs of scientists and non-academic actors, the desired outcomes as well as to available money and time (Durham et al 2014, Tobias et al 2018. Hence, there cannot be a TDR blueprint in terms of ''one-size-fits-all'' (Zscheischler and Rogga 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The respondents in this survey were those with whom we have experience collaborating, and who we knew to be open to collaboration between city administrations and researchers, so it is not surprising that the attitudes were generally positive. Tobias et al (2019) similarly found that experience with collaboration tends to lead to more positive attitudes towards transdisciplinary principles and to a higher likelihood of collaboration in the future. However, even within this group of colleagues with a history of working together, some differences in the working worlds were identi ed and there appear to be insu cient mutual understandings of the constraints they each face.…”
Section: Tensions In Collaborationmentioning
confidence: 83%
“…This will require that researchers become partners in knowledge creation rather than solely producers of knowledge and to recognise multiple ways of understanding drought risk. In the right collaborative environment, explicit interaction with different knowledge systems can help to build trust, develop shared understandings and enrich knowledge outcomes (Tobias et al, 2019). Creating an enabling environment that accommodates a diverse understanding of drought is far from straightforward, requiring skills not typically required in natural science.…”
Section: Resultsmentioning
confidence: 99%